Meta-analysis of integrative medicine in the treatment of irradiation cystitis (中西医结合治疗放射性膀胱炎的Meta分析) - SONG Jiangman (宋江曼); LIU Feifei (刘菲菲); LIAN Xiaojing (廉晓静) (Association of Integrative Nursing, 2023)
Objective　Methods The randomized controlled trials on the treatment of irradiation cystitis by integrated traditional Chinese and western medicine published by PubMed, Cochrane library, CBM, CNKI, VIP and Wanfang Database were searched by computer according to the inclusion criteria. The included literatures were meta-analyzed by Revman 5. 3 software. Results 7 standard RCT studies were included, including 382 patients, 188 in the test group (receiving combination of traditional Chinese and western medicine) and 194 in the control group(receiving western medicine). The total effective rate of the experimental group was higher than that of the control group in the treatment of irradiation cystitis, with a significant difference［OR=3. 62, 95% CI(2. 16, 6. 09), P<0. 01］. Publication bias analysis revealed bias. Conclusion The combined treatment of traditional Chinese and western medicine can improve the total effective rate in the treatment of irradiation cystitis, and the effect was better than the simple western medicine treatment. However, the sample size of the included study was small, and the quality of included literature was poor. More high-quality clinical studies are needed for further verification. Totally　To comprehensively evaluate the clinical efficacy and advantages of integrated Traditional Chinese and western medicine in the treatment of irradiation cystitis, and provide theoretical guidance for the clinical treatment of irradiation cystitis. (目的 综合评价中西医结合治疗放射性膀胱炎的临床疗效及优势, 为临床治疗放射性膀胱炎提供理论指导。方法 依据纳入标准, 计算机检索建库时间至2022年8月的PubMed、Cochrane library、中国生物医学文献数据库(CBM)、中国知网(CNKI)、维普中文科技期刊数据库(VIP)及万方数据库(Wanfang Data)发表的关于中西医结合治疗放射性膀胱炎的随机对照研究(RCT), 运用Revman 5. 3软件对纳入文献进行Meta分析。结果 符合标准的RCT 研究共7项, 共382例患者, 其中试验组188例, 对照组194例。中西医结合治疗为试验组, 单纯西医治疗为对照组。试验组较对照组治疗放射性膀胱炎的总有效率提高 ［OR=3. 62, 95% CI(2. 16, 6. 09), P＜0. 01］。发表偏倚分析显示存在偏倚。结论 中西医结合治疗放射性膀胱炎可以提高患者总有效率, 效果优于单纯的西医疗法。但纳入研究样本量偏少, 文献质量一般, 需要更多高质量临床研究进一步验证。)